2013
DOI: 10.1002/jhm.2073
|View full text |Cite
|
Sign up to set email alerts
|

Dear Doctor: A tool to facilitate patient‐centered communication

Abstract: BACKGROUND: Patient-centered care has been identified as 1 of the 6 aims for the 21st century healthcare system. The notepad is a simple tool for reminders and personal interactions. We introduced Dear Doctor (DD) notes, a bedside notepad designed to prompt patient questions and improve patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…Three studies evaluated the influence of visual tools on communication. 14,24,29 Using pictures, Appel et al 14 found no difference in the perceived quality of communication. Singh et al 29 used whiteboards and reported improved communication scores for physicians and nurses.…”
Section: Patient-provider Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies evaluated the influence of visual tools on communication. 14,24,29 Using pictures, Appel et al 14 found no difference in the perceived quality of communication. Singh et al 29 used whiteboards and reported improved communication scores for physicians and nurses.…”
Section: Patient-provider Communicationmentioning
confidence: 99%
“…Singh et al 29 used whiteboards and reported improved communication scores for physicians and nurses. With notepads, patients surveyed by Farberg et al 24 stated that the tool improved provider communication.…”
Section: Patient-provider Communicationmentioning
confidence: 99%
“…Because specific cancer treatments have been indicted in development of BI disturbances (Fingeret et al., 2014), understanding how BC treatment affects BI is essential for clinicians and this knowledge can increase effectiveness of treatment team (Male et al., 2016). Communication with patient is crucial in identifying and solving patient's problems with BI (Farberg et al., 2013; Venetis et al., 2009), and in this regard, patient‐centred communication (PCC) has been touted as a means of addressing BI issues, especially as it promotes listening on the part of the health caregiver which is considered to be therapeutic (Fingeret et al., 2014). It allows healthcare providers fashion out best care plan which gives room for active participation of patients (Epstein et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Communication with patient is crucial in identifying and solving patient's problems with BI (Farberg et al, 2013;Venetis et al, 2009), and in this regard, patient-centred communication (PCC) has been touted as a means of addressing BI issues, especially as it promotes listening on the part of the health caregiver which is considered to be therapeutic (Fingeret et al, 2014). It allows healthcare providers fashion out best care plan which gives room for active participation of patients (Epstein et al, 2005).…”
mentioning
confidence: 99%
“…6 The premise was that patients who are involved in their treatment plan are more likely to be satisfied with their overall hospital experience and have better outcomes. 7 Patient-centered care is now also in the public opinion arena. The Agency for Healthcare Research and Quality (AHRQ) developed the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey.…”
mentioning
confidence: 99%